An Analysis of Deixis on Whatsapp Conversation Between Postgraduate Student and Lecturers - Mulyadi Mulyadi (CV. Tripe Konsultan, 2023)
This current study aims at seeking the type of deixis often used by postgraduate student and lecturers. The writer applied a descriptive qualitative research method to explore the phenomena on student and lecturer interaction. Five conversations were collected from postgraduate students in which the text message from or to his lecturers. Screen shots of each conversation was taken so as to use it as it is on the WhatsApp. Then, those were analyzed on deixis Levinson theory. The research revealed that the occurrences of person deixis and address terms were prevalently committed. As the conclusion, the results of this study might become insight for students to know deixis and its type.